Vittorio Emanuele Orlando Italy - Di Scala, Spencer (Haus histories, 2010)
The Italian premier Vittorio Orlando came to Paris as one of the Big Four', yet in April 1919 walked out in one of the most dramatic crises of the Peace Conferences. This book also details the clash between Italy's territorial demands in the Balkans, which had been guaranteed by the Allies in 1915 and earned through her losses in the War.